THE EFFECT OF INFRASTRUCTURE, WORK MOTIVATION, NON-PHYSICAL WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PERUMDA AIR UMUM TIRTA BANGKA SUNGAILIAT AREA, BANGKA REGENCYl - Aulia, Kevin Aulia; Dian Prihardini Wibawa; Nurwasya (JAMBE: Jurnal Akuntansi Manajemen Bisnis dan Ekonomi, 2025)
This research is motivated by the performance of employees that have not been maximized, which is caused by factors that affect employees in an effort to achieve performance. This study aims to find out and analyze the Infrastructure, Work Motivation, Non-physical Work Environment on Employee Performance in PERUMDA Tirta Bangka Drinking Water Area, Sungailiat Area, Bangka Regency. This research is a quantitative descriptive research. The number of respondents in this study was 98 people, which was determined using the saturated sample method. The analysis model used is the multiple linear regression analysis model. The results of the study show that infrastructure, work motivation, and non-physical work environment partially have a positive and significant effect on the performance of employees at PERUMDA Tirta Bangka Drinking Water in the Sungailiat Area, Bangka Regency. The results of simultaneous tests of infrastructure, work motivation, and non-physical work environment together had a positive and significant effect on employee performance at PERUMDA Tirta Bangka Drinking Water in the Sungailiat Area, Bangka Regency.